Evaluation of Diagnostic Yield in Fetal Whole-Exome Sequencing: A Report on 45 Consecutive Families - Greenbaum, Lior; Pode-Shakked, Ben; Eisenberg-Barzilai, Shlomit; Dicastro-Keidar, Michal; Bar-Ziv, Anat; Goldstein, Nurit; Reznik-Wolf, Haike; Poran, Hana; Rigbi, Amihai; Barel, Ortal; Bertoli-Avella, Aida M.; Bauer, Peter; et al. (Frontiers in Genetics, 2019)
Prenatal ultrasound (US) abnormalities often pose a clinical dilemma and necessitate facilitated investigations in the search of diagnosis. The strategy of pursuing fetal whole-exome sequencing (WES) for pregnancies complicated by abnormal US findings is gaining attention, but the reported diagnostic yield is variable. In this study, we describe a tertiary center's experience with fetal WES from both terminated and ongoing pregnancies, and examine the clinical factors affecting the diagnostic rate. A total of 45 consecutive families of Jewish descent were included in the study, for which clinical fetal WES was performed under either single (fetus only), trio (fetus and parents) or quatro (two fetuses and parents) design. Except one, all families were non-consanguineous. In 41 of the 45 families, WES was sought following abnormal fetal US findings, and 18 of them had positive relevant family history (two or more fetuses with US abnormalities, or single fetus with US abnormalities and an affected parent). The overall diagnostic yield was 28.9% (13/45 families), and 31.7% among families with fetal US abnormalities (13/41). It was significantly higher in families with prenatal US abnormalities and a relevant family history (10/18, 55.6%), compared to families with prenatal US abnormal findings and lack of such history (3/23, 13%) (p=0.004). WES yield was high (46.2%-60%) among families with involvement of brain, renal or musculoskeletal US findings. Taken together, our results in a real-world setting of genetic counselling demonstrates that fetal WES is especially indicated in families with a positive family history, as well as in fetuses with specific types of congenital malformation.